Analisis Persepsi Mahasiswa Akuntansi Terhadap Independensi Auditor: (Studi Kasus Pada Mahasiswa Prodi D3 Akuntansi Politeknik Negeri Ambon) - Dynne Andriany; Julie Theresya Pelamonia (ISAS, 2026)
This study aims to analyze accounting students' perceptions of auditor independence. This study uses a qualitative method with a descriptive approach. Data collection techniques were conducted through an open questionnaire given to 6b semester accounting students as respondents. Data were analyzed using coding techniques including open coding, axial coding, and selective coding. The results of the study indicate that students have a good understanding of auditor independence as a mental attitude that is free from influence, objective, honest, and impartial. Auditor independence is considered very important because it is the basis of public trust in financial reports. Student perceptions of the condition of auditor independence in Indonesia indicate that it is generally quite good, but still faces various challenges such as business pressure, conflicts of interest, and long-term relationships with clients. Factors that influence auditor independence include audit fees, client relationships, management pressure, and the provision of non-audit services. Auditor independence can result in decreased public trust, errors in decision-making, and financial losses for users of financial reports. This study also found that professional ethics and auditing learning on campus play an important role in shaping students' understanding of auditor independence. Therefore, ongoing efforts are needed to strengthen professional ethics, improve the quality of auditing education, and enforce regulations to maintain auditor independence in the future. Keywords: auditor independence, student perceptions